Synthesis, characterization and catalytic activity of Ni supported on bleaching clay - Mohd Alias, Ahmad (2012)
Bleaching clay samples from Hudson WA Sdn Bhd were used to synthesis Ni(II) supported on clay. Metal supported on clay can serve as catalyst for hydrogenation reaction of crude palm oil. Acid analyses were employed using Ion Chromatography and titration technique to determine type and acid content. The nature of the bleaching clay examined by using X-ray Diffraction (XRI)), Thermal Gravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) and BET surface area. Nickel acetate with ethylene glycol as reducing agent was treated with bleaching clay to absorp metal: onto and into the interlayer of the clay. The adsorption of Ni(II) was investigated using BET surface area and x-ray diffraction. IC analysis and acid-base titration showed acid sulphuric as dominant acid at 0.0615 wt %. FTIR spectra and XRD pattern of this clay is identical with jute mineral It has a lattice spacing of 10.67 A and has primitive bravais lattice properties. As much as 20 wt% of nickel can be intercalated and supported to bleaching clay. Metal supported clay have low load capacity compared with metal intercalated clay. However, particle diameter and surface area are increasing from 90 A to 170 A and 600 m 2 /g to 800 m 2 /g when load capacity is increases. Reactivity of Ni(II) supported bleaching clay is low where percentage of saturated fatty acid increases by 1 % to 2.5 % in hydrogenation reaction of crude palm oil at room temperature and pressure.